Historic-archaeological research in the conservation of the building heritage of Cuenca (Ecuador): example of analysis Rodríguez house, El Vado neighborhood - Tómmerbakk Sorensen, María; Vargas Díaz, Juan Pablo; Herrera González, Esteban Alejandro (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
The international and national norms establish the need to count on historical information prior to an intervention in heritage properties and the Organic Law of Culture of Ecuador establishes the obligation to notify any discovery of archaeological interest. However, there is a lack of awareness regarding to the importance of these resources that in the moment they complement each other enable a more exact interpretation of the data required to promote an optimal conservation proposal and thus perpetuate the intrinsic values of a heritage building. The historical and archaeological investigation carried out in the Rodríguez house revealed that the property contains certain values of relevance for the sustainability of its environment and that the omission of these would deprive the restoration project of evaluation criteria and the community of important resources for the development of a resilient city.